Effect of different corundum sources on microstructure and properties of Al2O3–Cr2O3 refractories. Issue 15 (15th October 2019) - Pan, Dunxiang; Zhao, Huizhong; Zhang, Han; Zhao, Pengda; Li, Yichong; Zou, Qingfeng
Abstract: Al2 O3 –Cr2 O3 refractories are completely substitutional solid solutions and exhibit better corrosion and abrasion resistance. To enable the comprehensive utilization of it, the microstructure and properties of Al2 O3 –Cr2 O3 samples with different corundum sources were investigated in this study. The starting sources of corundum sources included sintered tabular corundum, fused white corundum, or brown corundum with minor impurities of β-Al2 O3 and TiO2 . The results of mechanical test showed that the introduction of white corundum deteriorates the physical structure, while brown corundum acts in an opposite manner. The optimum bonding strength of the Al2 O3 –Cr2 O3 brick was reached by combining white and brown corundum, whereby rapid neck growth occurred via surface diffusion during solid-phase sintering.